z-z(z+3)+3z=

Simple and best practice solution for z-z(z+3)+3z= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for z-z(z+3)+3z= equation:


Simplifying
z + -1z(z + 3) + 3z = 0

Reorder the terms:
z + -1z(3 + z) + 3z = 0
z + (3 * -1z + z * -1z) + 3z = 0
z + (-3z + -1z2) + 3z = 0

Reorder the terms:
z + -3z + 3z + -1z2 = 0

Combine like terms: z + -3z = -2z
-2z + 3z + -1z2 = 0

Combine like terms: -2z + 3z = 1z
1z + -1z2 = 0

Solving
1z + -1z2 = 0

Solving for variable 'z'.

Factor out the Greatest Common Factor (GCF), 'z'.
z(1 + -1z) = 0

Subproblem 1

Set the factor 'z' equal to zero and attempt to solve: Simplifying z = 0 Solving z = 0 Move all terms containing z to the left, all other terms to the right. Simplifying z = 0

Subproblem 2

Set the factor '(1 + -1z)' equal to zero and attempt to solve: Simplifying 1 + -1z = 0 Solving 1 + -1z = 0 Move all terms containing z to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1z = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1z = 0 + -1 -1z = 0 + -1 Combine like terms: 0 + -1 = -1 -1z = -1 Divide each side by '-1'. z = 1 Simplifying z = 1

Solution

z = {0, 1}

See similar equations:

| 0=4.9t^2+225.0 | | k(x^2+1)=x-k | | 56+6576=7563g+67757-5357476+456645gh | | 8(x+6)=8(x+15) | | 3(-5x-3)=-x-23 | | 4.7m=24.44 | | 15x-8y=128 | | 8x-6=48x-6 | | 6(a-6)=-6a-24 | | 3x-3x+10=1 | | 16x^10+2x^5+6=0 | | 7x+11=-7x-20 | | x/1/5-5=35 | | -7(5v-5)=280 | | .05x+.10(14-2x)+.25+(x+6)=3.3 | | 4+125x+5x^2=0 | | 7r^2+10r-8=0 | | 2x+26-7=x | | -4(1+7x)=-88 | | 4+125x+5t^2=0 | | 7(x+11)=7x+77 | | .25x+80-.50x=.40 | | 5x^6-2x^2+8=0 | | 3n+n-8=2n+4 | | 6q-p+8q-p= | | 3p+19=29-7p | | 8.02=3.1f-8.1 | | M-2=-16+3m | | Y=0.6-75 | | 7x-35-3x=4x-35 | | -2y^3(5xy^4)= | | 7r+4=8r-4 |

Equations solver categories